Comparative Genomic Analysis among Four Representative Isolates of Phytophthora sojae Reveals Genes under Evolutionary Selection - Ye, Wenwu; Wang, Yang; Tyler, Brett M.; Wang, Yuanchao (Frontiers in Microbiology, 2016)
Comparative genomic analysis is useful for identifying genes affected by evolutionary selection and for studying adaptive variation in gene functions. In Phytophthora sojae, a model oomycete plant pathogen, the related studies is lacking. We compared sequence data among four isolates of P. sojae, which represent its four major genotypes. These isolates exhibited >99.688%, >99.864%, and >98.981% sequence identities at genome, gene, and non-gene regions, respectively. 153 positive selection and 139 negative selection candidate genes were identified. Between the two categories of genes, the positive selection genes were flanked by larger intergenic regions, poorly annotated in function, and less conserved; they had relatively lower transcription levels but many genes had increased transcripts during infection. Genes coding for predicted secreted proteins, particularly effectors, were overrepresented in positive selection. Several RxLR effector genes were identified as positive selection genes, exhibiting much stronger positive selection levels. In addition, candidate genes with presence/absence polymorphism were analyzed. This study provides a landscape of genomic variation among four representative P. sojae isolates and characterized several evolutionary selection-affected gene candidates. The results suggest a relatively covert two-speed genome evolution pattern in P. sojae and will provide clues for identification of new virulence factors in the oomycete plant pathogens.